1996
DOI: 10.2337/diab.45.9.1279
|View full text |Cite
|
Sign up to set email alerts
|

Missense Mutation of Amylin Gene (S20G) in Japanese NIDDM Patients

Abstract: Many studies suggest that amylin, which is cosecreted with insulin from islet beta-cells, is a biologically active peptide and modulates plasma glucose levels. We therefore scanned the amylin gene for mutations in 294 Japanese NIDDM patients by single-strand conformational polymorphism, and we found a single heterozygous missense mutation (Ser-->Gly at position 20: S20G mutation) in 12 NIDDM patients (frequency 4.1%). None of the 187 nondiabetic subjects or 59 IDDM patients had the mutation. Of 12 patients car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(87 citation statements)
references
References 11 publications
6
81
0
Order By: Relevance
“…The naturally occurring mutation Ser20Gly (S20G) found in a small number of Asian diabetic patients (Sakagashira et al 1996, Lee et al 2001 has been shown to enhance amyloidosis and cytotoxicity in hIAPP S20G transgenic mice compared to hIAPP-native sequence transgenic mice (Meier et al 2016) and to accelerate fibril formation in vitro (Sakagashira et al 2000, Ma et al 2001, Figure 2 Structural models of the hIAPP protofibril. (A) A β-bend in regions 18-27 results in a horseshoe shaped structure with the N-and C-termini (N-term, C-term) on the same face.…”
Section: The Structure Of Iapp and Fibril Assemblymentioning
confidence: 99%
“…The naturally occurring mutation Ser20Gly (S20G) found in a small number of Asian diabetic patients (Sakagashira et al 1996, Lee et al 2001 has been shown to enhance amyloidosis and cytotoxicity in hIAPP S20G transgenic mice compared to hIAPP-native sequence transgenic mice (Meier et al 2016) and to accelerate fibril formation in vitro (Sakagashira et al 2000, Ma et al 2001, Figure 2 Structural models of the hIAPP protofibril. (A) A β-bend in regions 18-27 results in a horseshoe shaped structure with the N-and C-termini (N-term, C-term) on the same face.…”
Section: The Structure Of Iapp and Fibril Assemblymentioning
confidence: 99%
“…Amyloid fibrils were observed within WW and GW founders on both control and high fat diet as shown in the supplemental data (Appendix S2). It is important to note that the penetrance of the S20G mutation with premature onset type 2 diabetes is low and appears to be restricted to a genetic background predisposing to normal onset type 2 diabetes, 10 although it is unknown whether these genetic differences affect amyloidogenesis in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Asians with premature onset type 2 diabetes harbor a mutation in the h IAPP gene (S20G), providing a causal link between this gene and disease 10 . The mutation is rare affecting 1.9–2.6% of type 2 diabetics 11,12 and 0.8% of non‐diabetic control subjects 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Near relatives (especially first degree) suffering from type II increases risks of developing diabetes substantially in individuals. In addition, there is also a mutation to the Islet Amyloid Polypeptide gene that results in an earlier onset, more severe form, of diabetes (Wild et al, 1996;Cho, 2003). Exercise and life style modification plays significant role in the prevention of type II diabetes as well as in minimizing its complications (Bennion, 1979;Manson et al, 1991;Yamoka et al, 2005;Lindstrom et al, 2006); Li et al, 2008).…”
Section: Journal Of Biology and Life Sciencementioning
confidence: 99%